The Component of At-Taufiq Arabic-Java-Indonesia Multilanguage Dictionary on Dr. Ali Al Qasimy’s Perspective: Lexicography Approach - M. Khoiri; Rabiatul Hadawiyah; Ach. Faridhal Athros Al Farisi; Aminudin Aminudin (JURNAL ISLAM NUSANTARA, 2025)
This study reveals that the At-Taufiq Arabic–Javanese–Indonesian Multilanguage Dictionary only partially meets the structural components established by Dr. Ali Al-Qasimi. Several essential features are present, including a clearly stated purpose, semantic explanations, contextual usage examples, functional tables, and a historical chronology. However, important elements such as phonetic information, transliteration rules, detailed grammatical notes, appendices, maps, and biographical information about the compiler are absent. These findings indicate that the dictionary adopts a practical, pesantren-oriented approach that prioritizes usability for readers of classical Arabic texts rather than achieving full lexicographical completeness. Thus, the study affirms that dictionary usefulness is shaped not only by structural components but also by contextual relevance and alignment with user needs. This research provides the first systematic evaluation of the dictionary using Al-Qasimi’s framework, bridging theoretical lexicography with practical dictionary production in Islamic educational settings. Its qualitative design, however, limits generalizability and excludes empirical user testing. Future studies should compare multiple multilingual dictionaries and incorporate usability assessments to propose more standardized revisions. Strengthening missing components would enhance the At-Taufiq Dictionary’s academic value while preserving its functional strengths for learners.